A comparative analysis of the inflation hedging properties of gold, stocks, corporate bonds, and foreign currency in the Philippines from years 2011-2019 - de Jesus, Ma. Danielle Kyle L. (Animo Repository, 2021)
Inflation has a detrimental effect on developing countries due to its ability to obstruct economic growth. With this, the presence of inflation in financial markets has been a significant concern for stakeholders. In attempts to shield investors from inflation risk, literature regarding inflation hedging has been designed based on the Fisher (1930) theory. This study seeks to answer whether there is a significant relationship between inflation and financial assets, specifically gold, stocks, corporate bonds, and foreign currencies in the Philippines from 2011 to 2019. The proponents of this study primarily followed the method of Ndako and Salisu (2020). To decide empirically whether such a relationship exists, the following methods were implemented: Ljung Box Test, Autoregressive Conditional Heteroskedasticity (ARCH), Augmented Dickey-Fuller (ADF), Narayan and Liu (2015), Generalized Autoregressive Conditional Heteroscedasticity (GARCH) based tests, Bai and Perron (2003), and Autoregressive Distributed Lag (ARDL). The results reveal that the inflation hedging abilities of considered assets are heterogeneous. The Bond YTM proves to be a superior hedge against inflation, whereas the rest of the variables show no hedging ability against inflation.